Kaposiform hemangioendothelioma with satellitosis and Kasabach-Merritt phenomenon - Asit Mittal; Sharad Mehta; Vaishali Masatkar; Ashok K Khare; Lalit K Gupta (Wolters Kluwer Medknow Publications, 2016)
Kaposiform hemangioendothelioma is a rare, potentially life-threatening vascular tumor often associated with a coagulopathy known as Kasabach-Merritt phenomenon (KMP). We report the case of an infant with satellite lesions around a large vascular tumor and associated KMP.